The Genomic Revolution and Beliefs about Essential Racial Differences: A Backdoor to Eugenics? - Phelan, Jo C. (2013)
Could the explosion of genetic research in recent decades affect our conceptions of race? In Backdoor to Eugenics, Duster argues that reports of specific racial differences in genetic bases of disease, in part because they are presented as objective facts whose social implications are not readily apparent, may heighten public belief in more pervasive racial differences. We tested this hypothesis with a multi-method study. A content analysis showed that news articles discussing racial differences in genetic bases of disease increased significantly between 1985 and 2008 and were significantly less likely than non–health-related articles about race and genetics to discuss social implications. A survey experiment conducted with a nationally representative sample of 559 adults found that a news-story vignette reporting a specific racial difference in genetic risk for heart attacks (the Backdoor Vignette) produced significantly greater belief in essential racial differences than did a vignette portraying race as a social construction or a no-vignette condition. The Backdoor Vignette produced beliefs in essential racial differences that were virtually identical to those produced by a vignette portraying race as a genetic reality. These results suggest that an unintended consequence of the genomic revolution may be the reinvigoration of age-old beliefs in essential racial differences.